THE ROLE OF FREE EDUCATION TECHNOLOGY IN LITERARY EDUCATION - Pardabayeva Muqaddas Mirzamurod's daughter (Sciental Journals Publishing, 2025)
This article is about the role and importance of free education technology in literary education.
Keywords: Pedagogy, free education, technology, spirituality, educator,traditional education, the idea of humanity.